Strategies to Control Intention to Quit Safety Field (Phenomenological Study of a Nickel Smelter Company in Indonesia) - Qadri, M. Hasanul; Toto Raharjo, Susilo (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The rapid progress of business creates competitive competition, encouraging modern business industries to implement an Occupational Health Safety Environment (OHSE). Data on work accidents in Indonesia shows the need for attention to work safety aspects. Certifications such as SMK3 ISO 14001 and 45001 become investors' assessments of corporate governance. Employee intention to quit can significantly impact costs and organizational stability. The role of the safety field at PT XYZ as an accident supervisor and countermeasure is crucial. However, the increase in turnover in this field shows various challenges, including remote location and lack of management follow-up. This study highlights demographic variables, job satisfaction, and individual variables as potential causes of turnover. The research method used in this study is descriptive with a qualitative approach. Through the research, factors of dissatisfaction among safety field employees were found, such as the cost of leave travel, lack of trust in leaders, and differences in safety standards. These factors are the cause of the Intention to Quit. The HRGA Department's turnover handling involved recruitment strategies, increased comfort, and exit interviews. However, the implementation of HRGA programs is considered not optimal due to the immature condition of the company.